SIPOC-OI: a proposal for open innovation in supply chains - Thais Assis de Souza; Guilherme Alcântara Pinto; Luiz Guilherme Rodrigues Antunes; André Grützmann (Innovation & Management Review, 2023)
Purpose - Regarding the premises of open innovation (OI) in terms of knowledge sources, this paper aims to discuss how to manage the existing sources of knowledge in supply chains. Design/methodology/approach - An integrative review was developed focusing on studies related to supply chain and OI, seeking to understand the relationships between them, supporting the innovative discussion. Findings - The SIPOC-OI was proposed as a tool to support the management of knowledge sources present in the supply chain, promoting efficiency to the company and improving its innovative capacity. Research limitations/implications - The conceptual proposal should be empirically verified to understand the management tool's obstacles and benefits for a company's innovation performance. Additionally, it would be useful to understand the results of this proposal in the relationships between agents of the chain, as well as the direction (inbound, outbound or coupled). Additionally, relevant points were highlighted as future agendas. Practical implications - The point of view based on OI treats the collaboration's aspects and its benefits to agents, which becomes an essential factor in improving the entire chain's integration and performance. Originality/value - The analysis of the flow of knowledge in supply chains from an OI perspective is an innovation in theory. Besides, the multidisciplinary proposal is expressed in the framework developed as it is based on a tool from engineering. Supply chain competencies/mindset is important to develop OI as well as is the contrary - there is a mutual practical and theoretical relevance between the integration of the concepts.
Keywords: 650; Innovative capacity; Integrative review; Open innovation; SIPOC; Supply chain